Patient with joint pain at an outpatient appointment - A. L. Vertkin; M. M. Shamuilova; Yu. V. Sedyakina; G. Yu. Knorring; A. V. Nosova (Лечащий Врач)
Pathology of the musculoskeletal system and osteoarthritis, in particular, remain a frequent reason for seeking medical care in the outpatient setting. The article offers brief algorithms for the diagnosis and therapy of osteoarthritis for use at the outpatient stage of medical care.The authors note that at present, osteoarthritis is not an inevitable manifestation of aging of the body, with which has to be resigned to. Osteoarthritis should be diagnosed early in the development of the disease, namely, at the pre-radiological stage. As a diagnosis of structural changes in the joint (cartilage, synovium and ligaments) and assessment of the effectiveness of therapy, MRI research should be widely used. Osteoarthritis therapy is based on both non-drug methods and medication, while the basic therapy is based on symptomatic delayed-acting drugs for the treatment of osteoarthritis. At the same time, chondroitin sulfate and glucosamine, according to the results of numerous studies, have a moderate or significant effect on pain and functional mobility of joints in osteoarthritis, are safe and are characterized by a minimum of side effects. Qualitative long-term randomized controlled trials have demonstrated the ability of chondroitin sulfate and glucosamine to slow the progression of joint space narrowing in osteoarthritis. The use of a combination of these drugs has also been shown to prevent cartilage loss.